The hidden dangers: How obesity alters cardiac innervation and structure in Zucker rats - Rocha, Daniel Wellington; Dias, Fernanda Gosuen Gonçalves; Lovo, Júlia Correa; Gomes, Silvio Pires; Rici, Rose Eli Grassi; Schimming, Bruno Cesar [UNESP]; De Castro Sasahara, Tais Harumi [UNESP] (Spandidos Publications, 2024)
Obesity is classified as a non-communicable chronic disease, and the impetus for investigating the role of the sympathetic nervous system in obesity arises from its potential involvement in the development of cardiovascular, metabolic and renal complications commonly observed in obese individuals. Alterations in cardiac sympathetic nervous activity can cause structural and functional disruptions in the heart. For this reason, the aim of the present study was to investigate the association between heart innervation and its structure in a rat model of obesity. For this purpose, the left ventricular volume, the total volume of cardiac muscle fibers and the total volume of neurons in the stellate ganglion in obese Zucker rats were estimated using three-dimensional quantitative methods based on stereology, a more accurate and unbiased method of quantification. Cholesterol and triglyceride levels were also measured. The mean cholesterol level was 75.6 mg/dl in the control group and 145.16 mg/dl in the obese group. The mean triglyceride level was 30.36 mg/dl in the control group and 504.16 mg/dl in the obese group. The following quantitative results were obtained: A left ventricular volume of 1.25 cm3 for the control group and 1.60 cm3 for the obese group, a total volume of cardiac muscle fibers of 1.16 mm3 for the control group and 2.34 mm3 for the obese group, and a total volume of neurons in the stellate ganglion of 34.3×106 μm3 for the control group and 23.01×106 μm3 for the obese group. On the whole, the present study demonstrates that obese Zucker rats exhibit elevated cholesterol and triglyceride levels. Obesity induces cardiac structural alterations, characterized by an increase in cardiac lumen and ventricular wall thickness. In the nervous system, the total volume of neurons in the stellate ganglia decrease, suggesting a potential reduction in cardiac sympathetic activity. From a translational perspective, the present study has proven that the animal model used herein is a useful tool for investigating the interactions between the sympathetic nervous system and heart morphology in obesity. It may also prove to be useful for preventive and therapeutic measures for cardiovascular diseases in obese individuals.
Keywords: heart; left ventricle; nervous system; obesity